O Orkut e a terceira forma de sociabilidade - Jonatas Dornelles (Ciências Sociais Unisinos)
This paper discusses the virtual interaction platform made available by the Orkut system and relates it to other forms of sociability. It also presents the characteristics that generate that availability as well as the technical features that make the system seductive to the user. At the end, it advances some hypotheses about the reason why a major part of the visitors are Brazilians.